2016
DOI: 10.1128/jvi.00471-16
|View full text |Cite
|
Sign up to set email alerts
|

Human Cathelicidin Compensates for the Role of Apolipoproteins in Hepatitis C Virus Infectious Particle Formation

Abstract: Exchangeable apolipoproteins (ApoA, -C, and -E) have been shown to redundantly participate in the formation of infectious hepatitis C virus (HCV) particles during the assembly process, although their precise role in the viral life cycle is not well understood. Recently, it was shown that the exogenous expression of only short sequences containing amphipathic ␣-helices from various apolipoproteins is sufficient to restore the formation of infectious HCV particles in ApoB and ApoE double-gene-knockout Huh7 (BE-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…Accordingly, two research groups highlighted the role of α-helical structures in HCV morphogenesis. The authors demonstrated that expression of short sequences containing amphipathic α-helices derived from apolipoproteins but also of other proteins such as the human cathelicidin antimicrobial peptide is sufficient to rescue the production of infectious HCV particles in apolipoprotein knockout cells ( 49 51 ). Of note, a recently published paper showed that α-helices found in host-derived apolipoproteins and in NS1 of other Flaviviridae may have overlapping roles in the formation of infectious flaviviral particles ( 52 ).…”
Section: The Functional Role Of Apolipoproteins In the Hcv Life Cyclementioning
confidence: 99%
“…Accordingly, two research groups highlighted the role of α-helical structures in HCV morphogenesis. The authors demonstrated that expression of short sequences containing amphipathic α-helices derived from apolipoproteins but also of other proteins such as the human cathelicidin antimicrobial peptide is sufficient to rescue the production of infectious HCV particles in apolipoprotein knockout cells ( 49 51 ). Of note, a recently published paper showed that α-helices found in host-derived apolipoproteins and in NS1 of other Flaviviridae may have overlapping roles in the formation of infectious flaviviral particles ( 52 ).…”
Section: The Functional Role Of Apolipoproteins In the Hcv Life Cyclementioning
confidence: 99%
“…Patients with chronic hepatitis C often develop extrahepatic manifestations, and thus it may be feasible that the secretion of host proteins possessing amphipathic α‐helices could compensate for the role of exchangeable apolipoproteins in the production of infectious HCV particles. In another previous study, we showed that human cathelicidin hCAP18/LL‐37 (cathelicidin antimicrobial peptide [CAMP]), the only known member of the cathelicidin family of antimicrobial peptides (AMPs), plays a comparable role in the formation of infectious HCV particles with exchangeable apolipoproteins . Furthermore, it is possible that other host factors are involved in the formation of infectious HCV particles via a similar mechanism.…”
Section: Redundant Role Of Host‐derived Secretory Glycoproteins In Thmentioning
confidence: 99%
“…In another previous study, we showed that human cathelicidin hCAP18/LL-37 (cathelicidin antimicrobial peptide [CAMP]), the only known member of the cathelicidin family of antimicrobial peptides (AMPs), plays a comparable role in the formation of infectious HCV particles with exchangeable apolipoproteins. 32 Furthermore, it is possible that other host factors are involved in the formation of infectious HCV particles via a similar mechanism.…”
Section: Host-derived Secretory Glycoproteins In the Formation Of Hcvmentioning
confidence: 99%
“…Finally, a study performed by the group Matsuuraa supported the importance of α-helix domains for HCV particle assembly. Indeed, they demonstrated that the human cathelicidin antimicrobial peptide (CAMP), a protein containing amphipathic α-helices, is able to rescue HCV infectious particle formation, raising the possibility of extra-hepatic propagation of HCV in cells with low-level or no expression of apolipoproteins [105]. To summarize, exchangeable apolipoproteins possess redundant roles in the assembly of HCV through the interaction of the amphipathic α-helices with viral particles.…”
Section: Hcv Lifecycle Apolipoproteins and Lipoprotein Metabolismmentioning
confidence: 99%